The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1055/s-0032-1306327
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Strength and Endurance are Maintained during Moderate Dehydration

Abstract: This study investigated the effects of moderate dehydration (~2.5% body weight) on muscle strength and endurance using percutaneous electrical stimulation to quantify central and peripheral fatigue, and isolate the combined effects of exercise-heat stress and dehydration, vs. the effect of dehydration alone. Force production and voluntary activation were calculated in 10 males during 1 brief and 15 repeated maximal voluntary isometric contractions performed prior to (control) walking in the heat (35°C), immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
(19 reference statements)
1
15
0
Order By: Relevance
“…Of these, 28 [7, 8, 11-14, 17-20, 24, 25, 30-45] met all of the inclusion criteria, thereby producing a total of 85 individual studies and weighted mean treatment effects to investigate the impact of hypohydration on upper (6/85) and lower (10/85) body muscle endurance, upper (14/85) and lower (25/85) body muscle strength, muscle anaerobic power (9/85) and capacity (9/85), and vertical jumping ability (12/85). A total of 20 research manuscripts produced more than one weighted mean treatment effect, with Hayes and Morse [25] producing ten, Ftaiti et al [34] producing two, Wilson et al [45] two, Cheuvront et al [17] two, Bigard et al [8] two, Bijlani and Sharma [30] two, Bosco et al [31] two, Bosco et al [32] six, Caterisano et al [33] three, Greiwe et al [35] four, Gutierrez et al [36] six, Jacobs [37] six, Jones et al [13] two, Judelson et al [11] six, Kraft et al [38] two, Montain et al [39] two, Naharudin and Yusof [40] six, Periard et al [41] four, Viitasalo et al [44] four, and Webster et al [12] four effect estimates. The work of Naharudin and Yusof [40] and Caterisano et al [33] contained three different groups of participants, while that of Gutierrez et al [36] contained two different groups of participants.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 28 [7, 8, 11-14, 17-20, 24, 25, 30-45] met all of the inclusion criteria, thereby producing a total of 85 individual studies and weighted mean treatment effects to investigate the impact of hypohydration on upper (6/85) and lower (10/85) body muscle endurance, upper (14/85) and lower (25/85) body muscle strength, muscle anaerobic power (9/85) and capacity (9/85), and vertical jumping ability (12/85). A total of 20 research manuscripts produced more than one weighted mean treatment effect, with Hayes and Morse [25] producing ten, Ftaiti et al [34] producing two, Wilson et al [45] two, Cheuvront et al [17] two, Bigard et al [8] two, Bijlani and Sharma [30] two, Bosco et al [31] two, Bosco et al [32] six, Caterisano et al [33] three, Greiwe et al [35] four, Gutierrez et al [36] six, Jacobs [37] six, Jones et al [13] two, Judelson et al [11] six, Kraft et al [38] two, Montain et al [39] two, Naharudin and Yusof [40] six, Periard et al [41] four, Viitasalo et al [44] four, and Webster et al [12] four effect estimates. The work of Naharudin and Yusof [40] and Caterisano et al [33] contained three different groups of participants, while that of Gutierrez et al [36] contained two different groups of participants.…”
Section: Search Resultsmentioning
confidence: 99%
“…In this regard, Bigard et al [8] found that hypohydration accelerated the electromyographic (EMG) alterations associated with muscle fatigue during prolonged static contractions at 25 % of peak torque. However, one must note that studies have typically found hypohydration to have no statistically significant effect on voluntary muscle activation [11,18,24,41] or EMG responses during maximal voluntary static or isokinetic contractions [7,18,20,25] or during repeated and prolonged muscle contractions [34,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although hypohydration affects several aspects of peripheral physiology, current evidence suggests that body water losses do not impact efferent nerve signals destined to muscles. In fact, studies have typically found hypohydration to have no effect on voluntary muscle activation (Bowtell, Avenell, Hunter, & Mileva, 2013;Del Coso, Estevez, & Mora-Rodriguez, 2008;Judelson et al, 2007;Periard, Tammam, & Thompson, 2012), or electromyographic responses during maximal voluntary isometric or isokinetic contractions (Bowtell et al, 2013;Evetovich et al, 2002;Hayes & Morse, 2010;Minshull & James, 2013). To date, only one study has shown hypohydration to reduce electromyographic signal amplitudes during maximal isometric and isokinetic contractions of the knee flexors and extensors (Ftaiti, Grelot, Coudreuse, & Nicol, 2001).…”
Section: Neuromuscular Functionmentioning
confidence: 99%